Practice assistants in primary care in Germany: associations with organizational attributes on job satisfaction - Gavartina, Amina; Zaroti, Stavria; Szecsenyi, Joachim; Miksch, Antje; Ose, Dominik; Campbell, Stephen; Götz, Katja (BMC family practice, 2013)
Job satisfaction and organizational attributes in primary care teams are important issues as they affect clinical outcomes and the quality of health care provided. As practice assistants are an integral part of these teams it is important to gain insight into their views on job satisfaction and organizational attributes. The aim of this study was to evaluate the job satisfaction of practice assistants and the organizational attributes within their general practices in Germany and to explore the existence of possible associations.
Gesehen am 28.01.2020